2021
DOI: 10.4067/s0717-75182021000100009
|View full text |Cite
|
Sign up to set email alerts
|

Oral condition of institutionalized older people: influence on anthropometric indicators, food and nutrient intake

Abstract: Oral condition of institutionalized older people: influence on anthropometric indicators, food and nutrient intake Condición oral de las personas mayores institucionalizadas: influencia en los indicadores antropométricos y la ingesta de alimentos y nutrientes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Significant differences were also found in the age variable, where a higher consumption of fibre from fruit and vegetables was observed in older people and in women. With regard to the elderly and fibre consump-tion, our results and the scientific evidence indicate that consumption is below what is recommended by international organisations [62][63][64]; therefore, we should encourage the increased consumption of vegetable foods, fruit, and cereals that are rich in dietary fibre, as it has been shown that a good intake of this nutrient in the elderly can have positive effects on improving cognitive function, preventing depression [65,66], enhancing effects on muscle quality and function, and improving and maintaining occlusal strength [67]. All of the above can be associated with fibre's physicochemical and functional characteristics, especially those related to maintaining the balance of the intestinal microbiota [68], preventing a reduction in biodiversity and the overexpression of pathobionts.…”
Section: Discussionmentioning
confidence: 65%
“…Significant differences were also found in the age variable, where a higher consumption of fibre from fruit and vegetables was observed in older people and in women. With regard to the elderly and fibre consump-tion, our results and the scientific evidence indicate that consumption is below what is recommended by international organisations [62][63][64]; therefore, we should encourage the increased consumption of vegetable foods, fruit, and cereals that are rich in dietary fibre, as it has been shown that a good intake of this nutrient in the elderly can have positive effects on improving cognitive function, preventing depression [65,66], enhancing effects on muscle quality and function, and improving and maintaining occlusal strength [67]. All of the above can be associated with fibre's physicochemical and functional characteristics, especially those related to maintaining the balance of the intestinal microbiota [68], preventing a reduction in biodiversity and the overexpression of pathobionts.…”
Section: Discussionmentioning
confidence: 65%